Pengurangan Diskriminasi Terhadap Penyandang Disabilitas dalam Tanggap Bencana: Studi Kasus Program SINAR PELITA di Kabupaten Aceh Tamiang - Putranto, Nurseno Dwi; Diltha, Khairunnisa; Isda, Dzakyansyah Naufal (Journal of Administration, Governance, and Political Issues, 2024)
This study aims to reduce discrimination against persons with disabilities in disaster response in Aceh Tamiang Regency through the Corporate Social Responsibility (CSR) program of PT Pertamina EP Rantau, known as the SINAR PELITA Program. The program implements an inclusive and responsive disaster management system by actively involving persons with disabilities. The research adopts a qualitative phenomenological approach using purposive sampling from members of the Digdaya Task Force, which is a key component of the SINAR PELITA Program. Key initiatives under this program include the formation of the Digdaya Task Force, emergency productive economic activities, and the use of Smart Current Meters and solar-powered systems as an Early Warning System (EWS). The findings indicate that the SINAR PELITA Program has successfully enhanced accessibility and reduced discrimination against persons with disabilities during disasters. In conclusion, the active participation of persons with disabilities in disaster response through the Digdaya Task Force is a significant step toward fostering a more inclusive environment. The program is expected to continue evolving, extending its benefits through initiatives such as the development of micro, small, and medium enterprises (MSMEs) based on food crops, the digitalization of program data, and strengthening the Digdaya Task Force as agents of change within the community.